A case of CLL that was successfully treated resulted in the immediate development of AML from a coexistent myeloid line that had been suppressed. Issue 3 (22nd December 2014) - Ansari, Mohammad; Auerbach, Michael; Bahrain, Huzefa
Key Clinical Message An 83 year‐old Caucasian male presented to the emergency room with confusion and lethargy. A complete blood count revealed lymphocytosis, anemia, and thrombocytopenia. A bone marrow examination revealed chronic lymphocytic leukemia (CLL), along with a small population of abnormal immature myeloid cells. Chemotherapy for CLL was started. After one cycle, repeat bone marrow examination revealed normalization of the lymphocyte count and a proliferation of the previously noted myeloid population, consistent with acute myeloid leukemia (AML). This report presents the microscopic, immunophenotypic, and cytogenetic evidence to document the development of AML after one cycle of chemotherapy for CLL.